Ceratosaurus (Theropoda, Ceratosauria) teeth from the Tacuarembó Formation (Late Jurassic, Uruguay). (November 2020) - Soto, Matías; Toriño, Pablo; Perea, Daniel
Abstract: Isolated theropod teeth from the Tacuarembó Formation (Late Jurassic of Uruguay) are comprehensively described. Several features (mesial teeth with restricted mesial carina not twisted lingually, presence of lingual flutes, labially displaced distal carina, DC between 9 and 12.5) allow the assignment to the genus Ceratosaurus . This referral is supported by multivariate and phylogenetic analysis. Similarities with spinosaurid teeth are discussed, and the identification of Jurassic teeth from Niger and Tanzania as members of Spinosauridae is questioned, being referred herein to Ceratosauridae. Hence, the family was widespread in the Jurassic of Gondwana. The presence of Ceratosaurus is, along with recently identified Torvosaurus teeth, another evidence of the Late Jurassic age of the fossiliferous horizons of the Tacuarembó Formation. Highlights: We describe a large theropod from Uruguay represented by isolated teeth. Detailed morphological analysis strongly resembles the ceratosaurid Ceratosaurus . Multivariate and phylogenetic analyses support this referral. We propose that the enigmatic Ostafrikasaurus crassiserratus from Tanzania should also be referred as a ceratosaurid theropod. We propose several scenarios of evolution of spinosaurid teeth.